(untitled) (Research, Society and Development, 2024)
This work presents an analysis of the importance and performance of photovoltaic systems (PV) connected to the electrical grid in a freshwater shrimp farm located in the interior of Ceará. Shrimp farming is expanding in the semi-arid region and one of the ways to make the business sustainable is to invest in renewable energy sources, especially solar, due to its environmental and economic benefits, since the region under analysis presents favorable conditions for the generation of solar and wind energy. The objective of the work is to carry out a performance analysis study of a photovoltaic microgeneration connected to the grid with a power of 42.88 kWp, installed in the interior of Russas-CE. For this study, production analyzes are carried out including energy generation, productivity, system losses, performance rate and capacity factor, based on electrical measurements generated by the inverter application and meteorological data provided by FUNCEME (2023). The results indicate that energy production is significantly influenced by solar irradiation and ambient temperature, with the months of August, September and October being the most productive. The productivity of the systems PV is analyzed in comparison with the reference irradiation, showing variations over the months. Furthermore, system losses and their influence on the performance rate are discussed, and measures to improve system efficiency are suggested. Finally, the study highlights the viability and efficiency of the analyzed systems PV, contributing to the sustainable development of the region.